Quest for the Phoenicians - Caragol, Pamela; Bredar, John B.; Cerveris, Michael; Zakin, Robert; Kane, David; Lyall, Robert; National Geographic Society (U.S.).; National Geographic Television & Film. ([Washington, D.C.] National Geographic Television & Film, 2006)
"Their sea-faring skills and vast trading network were the envy of the ancient world. But even today, the fabled Phoenicians remain a people shrouded in legend. Now, unravel a 3,000-year-old mystery as you join National Geographic on the Quest for the Phoenicians."--Container.
Introduction -- A ship of Reconciliation -- Uncontaminated DNA -- Caanaites and the sea peoples -- Cedars of Lebanon -- Religious controversy -- Secrets at Gibralter -- Discovery at the temple -- More serious problems -- The next best thing -- Genetic conclusion -- End credits.
Library has: VDR-1352 (1 DVD)
Originally broadcast as a National Geographic Special in 2004.
"Special features include photo gallery, map of Phoenicia, recommended programs"--
Editor, Robert Zakin ; music, David Kane ; cinematography, Robert Lyall ; narrator, Michael Cerveris.
Narrator, Michael Cerveris.
DVD format; region 1; standard version presented in a format preserving the aspect ratio of its original television exhibition ; Dolby Digital.
Keywords: Phoenicians; Documentary television programs; Films for the hearing impaired; Phoenicia -- Civilization